MОRPHОGICAL FEATURE ОF THE GALL BLADDER WALL ОF THE WILD BIRDS ОF PREY - Рябушко, О.Б. (World of Medicine and Biology, 2014)
As the results of our research, the structure of the gallbladder of birds of prey (Eurasian sparrowhawk ) is greatly simplified compared to omnivorous and herbivorous birds. Study of the gallbladder bottom shows a significant thinning of the entire wall. It is mainly due to external (muscle) membrane and lamina propria mucosae, but this membrane well defined in this section of the gallbladder.The most significant differences are peculiar to the inner surface of relief. It is observed significantly fewer villous protrusions. Their height and width greatly reduced. At the same time, the number of microvessels in most villi is quite sufficient. In some fibers they occupy a central part and arranged along the axis. In addition, microvascular elements are located in the middle and outer membranes on the gallbladder wall bottom.Study of gallbladder wall pays attention to the inner surface relief features. The relief of the surface has a shape unlike other birds. In this case, the number of villous protrusion per unit area of the wall gradually decreases from the bottom to the body of the gallbladder. At the same time, a gradual decrease in the size of villous protrusion has observed too. Lamina propria mucosae is tightened. In some areas a tighteness is replaced by fiber separation. Smooth outer membrane has a compacted form too. We have not seen lymph follicles in a gallbladder wall and bottom . The wall of the neck of Eurasian sparrowhawk gallbladder generally has an unusual structure. In its inner surface sometimes some low triangular-shaped protrusions can be found. In large areas a wall relief is quite flat and smooth. The base of protrusion is a loose lamina propria mucosae. In some fibers a few small thin-walled vessels can be seen. These vascular structures are found in the middle membrane wall of the neck. The outer smooth muscle membrane in contact with the loose subserous plate. It has much adipose tissue containing neurovascular bundles. The structure of the gallbladder wall birds of prey (on example of Eurasian sparrowhawk ) has significant differences compared with the structure of herbivorous and omnivorous walls birds. All elements of the histological structure of the gallbladder walls of predators look like atrophy. It appears as bladder wall in all areas is considerably tightened and thinned, especially in muscle layer. The number and size of villous structures significantly reduced compared with the previous birds. Along with these features of the gallbladder wall of birds of prey it should be noted decrease in the number of follicles in sections of lymph, which, in this case, localized in mildly expressed lamina propria mucosae. In villous protrusion these formations are not found in our materials. Presence of the large number of lymph follicles in the lamina propria mucosae and also in thickness of villous protrusion of the birds gallbladder wall undoubtedly indicates their origin. At large magnification of the microscope we can see that these follicles are composed of clusters of small lymphocytes separated from surrounding tissues, primarily from surface epithelium, compacted by tightened fibrous structures looked vaguely like capsules. Between them, oftenly, a slit-shaped cavity can be seen.
Keywords: gallbladder; cystic duct; cholecystitis; cholelithiasis